Demographic differences in Jordanian bank service quality perceptions. Issue 2 (3rd April 2017) - Al-jazzazi, Akram; Sultan, Parves
Abstract : Purpose: The purpose of this paper is to assess differences in banking service quality (BSQ) perceptions across demographic subgroups of Islamic and conventional Jordanian banking consumers. Design/methodology/approach: Data are collected using surveys. The survey contains items for three different measures of overall BSQ perceptions. The researchers mailed surveys to a random sample of 2, 000 banking customers in Jordan. Responses to questionnaire items measuring respondents' BSQ perceptions were analysed using one-way analysis of variance with Tukey's honest significant difference post hoc tests to assess subgroup differences in six demographic variables: gender, age, occupation, income, education, and religion. Findings: BSQ perceptions are significantly different in four of the six demographic variables. Age and education do not impact on BSQ perceptions. Research limitations/implications: The findings indicate demographic effects on Jordanian banking consumers' perceived BSQ. Study limitations include demographic subgroup underrepresentation and survey structure. Future research should obtain a more representative sample for better generalisability. Practical implications: The findings suggest that Jordanian banks should structure their services to best accommodate their customers' demographics. In addition, banks can use the findings to guide the development of demographic-driven marketing to target and attract customers efficiently. Originality/value: This study is the first to investigate demographic differences in the perceived service quality of Jordan's Islamic and conventional banking customers. The findings can contribute to future research on BSQ, and guide Jordan's banking management towards more effective marketing and service provision.